P728 Correlates of syphilis in women living with and without HIV in the US women's interagency HIV study (WIHS). (14th July 2019) - Aaron, Kristal; Brill, Ilene; Causey, Zenoria; Murphy, Kerry; Augenbraun, Michael; Kassaye, Seble; Milam, Joel; Seidman, Dominika; French, Audrey; Gange, Stephen; Adimora, Adaora; Sheth, Anandi; et al.
Abstract : Background: Population-based estimates of syphilis seroprevalence and risk factors for US women are lacking. The objective of this study was to examine the prevalence of syphilis and associated characteristics among women living with and without HIV in the Women's Interagency HIV Study (WIHS). Methods: Women enrolled in the multisite US WIHS Cohort Study between 1995 and 2016 were screened for syphilis at baseline using rapid plasma reagin (RPR) and confirmatory treponemal antibody testing. Prevalent syphilis was defined by a positive RPR and positive confirmatory test. Baseline characteristics among seropositive participants were compared with and without stratification by HIV status. Chi-square testing was used for comparisons for categorical variables while ANOVA or the Kruskal-Wallis test was used to test continuous variables. Multivariable logistic regression modeling with Firth's bias correction for prediction of syphilis seroprevalence was performed using baseline covariates from the non-stratified characteristics that were statistically significant at p<0.05. Results: Nearly 5, 000 women (n=4, 906) age 16–57 were included in the analysis: 3, 622 women with HIV and 1, 284 women without HIV. The prevalence of syphilis in women with HIV (7.6%) was higher compared to women without HIV (4.6%), p<0.001. Characteristics associated with syphilis infection at the baseline cohort visit (p<0.05) included positive HIV status [adjusted odds ratios and 95% confidence intervals, OR, (95%CI)], [1.49 (1.09–2.04)], black race compared to white, [3.32 (2.06–5.36)], <12 th grade education [1.72 (1.24–2.38)], income <$12, 000 [1.46 (1.08–1.97)], and history of transactional sex [2.61 (1.98–3.43)]. Conclusion: In the midst of a resurgence of syphilis infections in the US, factors associated with syphilis in women can help guide screening practice in clinic. This data from the WIHS cohort highlights the need for providers to consider HIV status, race, transactional sex and socioeconomics in order to identify women in need of routine syphilis screening. Disclosure: No significant relationships.